KESADARAN LINGKUNGAN TERHADAP GAYA HIDUP SEHAT BERPENGARUH PADA KEPUTUSAN PEMBELIAN PRODUK RAMAH LINGKUNGAN DI KALANGAN MILENIAL KOTA JAMBI - SIREGAR, AKHMAD IRWANSYAH; ALBETRIS, ALBETRIS (LP2MTBM MAKARIOZ, 2023)
This study was basically carried out on the basis of the author's concern with the current environmental conditions, which are increasingly worrying due to the increasing number of food consumption products, manufactured products, and services that are considered to be the main cause of environmental damage. The problem of this research centres on the lack of research that determines whether environmental awareness plays a role as a predictor in influencing people's healthy lifestyles, which have an impact on purchasing decisions for environmentally friendly products. Considering this, an important research question that needs to be answered is: Can environmental awareness influence the healthy lifestyle of the millennial generation, which has an impact on purchasing decisions for environmentally friendly products? The sample in this study was 105 respondents. This research uses a survey method with a quantitative descriptive approach, with environmental awareness as a predictor of a healthy lifestyle and purchasing decisions. Meanwhile, the data analysis used in this study was done through Partial Least Squares (PLS). However, before analysis, the outer model is first tested through validity and reliability tests. Next, carry out the inner model test through the R-square (coefficient of determination) and F-square (f2 effect size) tests. The results of this study conclude that environmental awareness has an influence on the decision to purchase environmentally friendly products among millennials in Jambi City, both directly and indirectly, through a healthy lifestyle